Legal Protection for Children in School Environments - Maemunah Maemunah; Novi Aryani; Abdul Sakban (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the implementation of legal protection policies for children in schools. The research design used a qualitative approach with a normative juridical approach. Data were collected through observation, in-depth interviews with teachers, students, and parents, as well as document analysis. Findings indicate that the school has successfully established a safe and supportive learning environment characterized by respectful teacher-student interactions, non-violent classroom management, and a strong sense of security among students. Guidance and counseling services serve as the primary mechanism for early detection, psychosocial support, and conflict mediation. At the same time, the School Violence Prevention and Response Team ensures structured case management aligned with national standards. Prevention programs, including human rights awareness campaigns, anti-bullying campaigns, and character development initiatives, raise student awareness of reporting mechanisms and foster a culture of mutual respect. Despite these achievements, the study identified significant obstacles, including inadequate teacher training, limited parental understanding of child protection procedures, a lack of adequate visual outreach materials, and challenges inherent in the rural educational context.